2020
DOI: 10.1111/cns.13396
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intra‐ and inter‐tumoral heterogeneity on molecular characteristics of primary IDH‐wild type glioblastoma revealed by single‐cell analysis

Abstract: Aims To reveal the effects of intra‐ and inter‐tumoral heterogeneity on characteristics of primary IDH‐wild type glioblastoma cells. Methods Single‐cell RNA‐seq data were acquired from the GEO database, and bulk sample transcriptome data were downloaded from the TCGA database with clinical information. Neoplastic subtype and glioma stem‐like cells (GSCs) were identified by matching 5000 random virtual samples based on ssGSEA. CNV was inferred to compare the heterogeneity among patients and subtypes by infercnv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…First, the current rat model of glioblastoma was produced by inoculation of the C6 cell line, which does not reflect the intra‐ and inter‐tumoral heterogeneity on molecular characteristics and sensitivities to therapies. 49 While it has been a considerable challenge in the field to inoculate primary glioblastoma cells into rodent brain, we will need to establish such models in the future to identify the optimal treatment paradigms for TEFT. Second, the side effects of TEFT were only partially studied in the current study, with a focus on local skin reactions.…”
Section: Discussionmentioning
confidence: 99%
“…First, the current rat model of glioblastoma was produced by inoculation of the C6 cell line, which does not reflect the intra‐ and inter‐tumoral heterogeneity on molecular characteristics and sensitivities to therapies. 49 While it has been a considerable challenge in the field to inoculate primary glioblastoma cells into rodent brain, we will need to establish such models in the future to identify the optimal treatment paradigms for TEFT. Second, the side effects of TEFT were only partially studied in the current study, with a focus on local skin reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Single-cell RNA-Seq (scRNA-Seq) analysis has emerged as an important approach to dissect the cellular and molecular profile of complex tumors compared to bulk conventional analysis. scRNA-Seq has yielded insights into phenotypic and genotypic differences resulting from tumor cells, the relation with the neural lineages, and the tumor microenvironment, and subpopulations of transformed cells in these extremely heterogeneous tumors (63,(70)(71)(72). Analysis of scRNA-Seq suggested that GBM consist of a combination of tumor cells with different GBM subtype footprints (63).…”
Section: Hgg Intertumoral and Intratumoral Molecular Heterogeneitymentioning
confidence: 99%
“… 34 , 35 Glioblastoma is viewed as an aggressive tumor with substantial heterogeneities. 36 Sottoriva et al performed a complete genomic analysis on biopsies of various parts of the tumors from 11 glioblastoma patients. The results revealed extensive intratumoral heterogeneities.…”
Section: Glioblastomamentioning
confidence: 99%